2016
DOI: 10.1002/hpm.2355
|View full text |Cite
|
Sign up to set email alerts
|

Continuous improvement, burnout and job engagement: a study in a Dutch nursing department

Abstract: Continuous improvement (CI) programs are potentially powerful means to improve the quality of care. The more positive nurses perceive these programs' effects, the better they may be expected to cooperate. Crucial to this perception is how nurses' quality of working life is affected. We studied this in a nursing department, using the job demands-resources model. We found that two job demands improved, and none of the job resources. Job engagement did not change significantly, while the burnout risk decreased sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
1
11
0
3
Order By: Relevance
“…Opportunities for learning and participation appear to have been affected by the fact that the studied company was midsize and family owned, that most people met each other every day, that most of the shop‐floor workers were skilled crafts people with qualified jobs, and that they were engaged in small‐lot production rather than production‐line work. This is in keeping with the suggestion by Benders, Bleijerveld, and Schouteten () that different task environments may differently affect the impact of lean on working conditions. The company was also in an expansion phase wherein they were developing new products and receiving increasing numbers of orders for special products.…”
Section: Discussionsupporting
confidence: 91%
“…Opportunities for learning and participation appear to have been affected by the fact that the studied company was midsize and family owned, that most people met each other every day, that most of the shop‐floor workers were skilled crafts people with qualified jobs, and that they were engaged in small‐lot production rather than production‐line work. This is in keeping with the suggestion by Benders, Bleijerveld, and Schouteten () that different task environments may differently affect the impact of lean on working conditions. The company was also in an expansion phase wherein they were developing new products and receiving increasing numbers of orders for special products.…”
Section: Discussionsupporting
confidence: 91%
“…In a study at two hospital departments in Denmark, Hasle [17] found contrasting effects depending on the type of changes proposed in the CI program. In a longitudinal study in a Dutch hospital department, Benders et al [18] found only minor changes, although those found were improvements. In this case, only a limited number of employees had taken the lead in the improvement efforts and the measurements were just three months apart, which may explain that the changes were minor.…”
Section: Introductionmentioning
confidence: 94%
“…In line with earlier work [18], we used the job demands-resources model [19] as the framework to map job characteristics. The job demands-resources model proposes that demanding aspects of work (job demands) lead to exhaustion (burnout), and that job aspects that help to achieve work goals (job resources) reduce the effect of job demands or stimulate personal growth and development resulting in work engagement (see further below).…”
Section: Introductionmentioning
confidence: 99%
“…The alignment of strategy, processes, structures, and activities formed a stable entity, all of which have been proposed as being important for health in an organization (von Thiele Schwarz & Hasson, 2013) and for sustainable lean initiatives (Hines, 2011). Since lean may impact work environments differently during different tasks (Benders et al, (2016), the fact that the present company engaged in small-scale skilled production rather than less skilled production-line work may have contributed to the positive outcomes seen in the results. Most previous studies of lean in industry reporting negative impacts on the work environment have studied less qualified industrial tasks.…”
Section: Contextual Factors Influencing Sswcmentioning
confidence: 99%